The Growth of an Electrochemical Garden on a Zinc Electrode. Issue 3 (4th February 2021) - Spanoudaki, Dimitra; Pavlidou, Eleni; Sazou, Dimitra
Abstract: The far‐from equilibrium precipitation reaction of chemical gardens can lead to the formation of biomimetic and complex structures providing a new route for the rational architectural design of functional materials. Inspired by recent developments in the field of chemical gardens, we put forward a new scientific question: "Is it possible to create an electrochemical garden?" By implementing state‐of‐the‐art electrochemical techniques and using the phenomenon of metal corrosion, we sculpture self‐organized structures on a zinc disc‐electrode surface by a mechanism similar to that of chemical gardens. A deeper search in the formation mechanism reveals that ion‐selective membranes are the driving force for the growth of an electrochemical garden. At last, electrochemical instabilities, introduced under proper conditions, result in the emergence of current oscillations in the region where electrochemical gardens were discovered. Current oscillations sculpture the electrode surface with a variety of self‐organized precipitate structures. Abstract : The birth of an electrochemical garden : The far‐from‐equilibrium precipitation reaction of chemical gardens is intensively studied due to the biomimetic, complex precipitate structures it creates. In this work, we use electrochemical corrosion of metals to sculpt, in a controllable way, complex structures on the surface of a zinc disc electrode, mimicking the growth mechanism of chemical gardens. This research can open new routes for smart design sculpturing of electrode surfaces for applications in optics, catalysis and sensing.